A Study on Ethical Hacking (International Journal of Innovative Research in Computer Science & Technology, 2022)
Though all material is now available  online, numerous individuals are using it; most are using it  to learn things, while many others are using it to educate  both how to harm or stealing information from websites or  networks without such owner’s permission. The purpose  of this essay is to define hacking, who programmers seem  to be, what vulnerability assessment is, what ethically  hacking's code of conduct is, but also why browser  hijackers are required. The Linux kernel is briefly  described in detail.. All of the methods are carried out on  the Kali Linux operating system. Following that, the article  discusses phishing attacks and denial of service attacks  (Denial of Services Attack). In addition, the paper  discusses what Wi-Fi is, how to secure Wi-Fi networks,  and how hackers crack Wi-Fi passwords. This paper is  very useful for future work as researcher can use this paper  for their survey.
Keywords: Computer; Data; Ethical Hacking; Hacker; Security